Regulation of cardiac microRNAs induced by aerobic exercise training during heart failure - Souza, Rodrigo Wagner Alves [UNESP]; Fernandez, Geysson J. [UNESP]; Cunha, João P. Q. [UNESP]; Piedade, Warlen Pereira [UNESP]; Soares, Luana Campos [UNESP]; Souza, Paula Aiello Tomé [UNESP]; Campos, Dijon Henrique Salome de [UNESP]; Okoshi, Katashi [UNESP]; Cicogna, Antonio Carlos [UNESP]; Dal-Pai-Silva, Maeli [UNESP]; Carvalho, Robson Francisco [UNESP] (American Journal of Physiology - Heart and Circulatory Physiology., 2015)
Exercise training (ET) has beneficial effects on the myocardium in heart failure (HF) patients and in animal models of induced cardiac hypertrophy and failure. We hypothesized that if microRNAs (miRNAs) respond to changes following cardiac stress, then myocardial profiling of these miRNAs may reveal cardio-protective mechanisms of aerobic ET in HF. We employed ascending aortic stenosis (AS) inducing HF in Wistar rats. Controls were sham-operated animals. At 18 weeks after surgery, rats with cardiac dysfunction were randomized to 10 weeks of aerobic ET (HF-ET) or to a heart failure sedentary group (HF-S). ET attenuated cardiac remodeling, as well as clinical and pathological signs of HF with maintenance of systolic and diastolic function when compared to HF-S. Global miRNA expression profiling of the cardiac tissue revealed 56 miRNAs differentially regulated in animals in the HF-ET, but only 12 miRNAs were differentially regulated in the HF-S. Out of 23 miRNAs that were differentially regulated in both groups, 17 miRNAs exhibited particularly high increases in expression, including miR-598, miR-429, miR-224, miR-425, and miR-221. From the initial set of deregulated miRNAs, 14 miRNAs with validated targets expressed in cardiac tissue that respond robustly to ET in HF were used to construct a miRNA-mRNA regulatory networks that revealed a set of 203 miRNA-target genes involved in programmed cell death, TGF-β signaling, cellular metabolic processes, cytokine signaling, and cell morphogenesis. Our findings reveal that ET attenuates cardiac abnormalities during HF by regulating cardiac miRNAs with potential role in cardio-protective mechanisms through multiple effects on gene expression.
Keywords: Aortic stenosis; Cardiac stress; Exercise training; Heart failure; Stress-regulated mirnas